2019
DOI: 10.48550/arxiv.1906.05965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Partitioned Finite Element Method for power-preserving discretization of open systems of conservation laws

Flávio Luiz Cardoso-Ribeiro,
Denis Matignon,
Laurent Lefèvre

Abstract: This paper presents a structure-preserving spatial discretization method for distributed parameter port-Hamiltonian systems. The class of considered systems are hyperbolic systems of two conservation laws in arbitrary spatial dimension and geometries. For these systems, a partioned finite element method is derived, based on the integration by parts of one of the two conservation laws written in weak form. The nonlinear 1D Shallow Water Equation (SWE) is first considered as a motivation example. Then the method… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…(A2) Sufficiently smooth solutions (ρ, w) and (ρ, ŵ) to the system (1)-( 5) exist for parameters 0 ≤ ε, ε ≤ ε and 0 < γ ≤ γ, γ ≤ γ with γ, γ constant, which satisfy ρ ≤ ρ, ρ ≤ ρ and − w ≤ w, ŵ ≤ w. (8) Conditions (A1) and (A2) imply uniform bounds for P and its derivatives and ensure that the flow is subsonic; we refer to [6] for details. Under these conditions, we will show the following stability result: Let (ρ, w) and (ρ, ŵ) be sufficiently regular solutions of (1)- (3) with parameters ε, γ and ε, γ, and boundary values ĥ∂ and h ∂ as described in (6). Then…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…(A2) Sufficiently smooth solutions (ρ, w) and (ρ, ŵ) to the system (1)-( 5) exist for parameters 0 ≤ ε, ε ≤ ε and 0 < γ ≤ γ, γ ≤ γ with γ, γ constant, which satisfy ρ ≤ ρ, ρ ≤ ρ and − w ≤ w, ŵ ≤ w. (8) Conditions (A1) and (A2) imply uniform bounds for P and its derivatives and ensure that the flow is subsonic; we refer to [6] for details. Under these conditions, we will show the following stability result: Let (ρ, w) and (ρ, ŵ) be sufficiently regular solutions of (1)- (3) with parameters ε, γ and ε, γ, and boundary values ĥ∂ and h ∂ as described in (6). Then…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, this formulation allows us to incorporate boundary conditions more naturally and to extend our results to networks in a straight-forward manner using appropriate coupling conditions at network junctions [24,9] that guarantee energy conservation or dissipation at network junctions. Similar formulations for compressible flow were also considered in the context of port-Hamiltonian systems; see [27,26] for the models and [3,19] for corresponding discretization strategies. Other systems, that fit into the general framework that we develop in this paper include the Euler-Korteweg system, the system of quantum hydrodynamics and the Euler-Poisson equations.…”
Section: Introductionmentioning
confidence: 99%
“…A spatial discretization method is structure preserving if the resulting concentrated parameter system can be written in ISO form (1). We use PFEM, as proposed by Cardoso-Ribeiro et al [25], for reasons outlined in the introduction. In particular, due to its straightforward applicability and compatibility with standard FEM methods and software.…”
Section: Spatial Discretizationmentioning
confidence: 99%
“…It seems that the Partitioned Finite Element Method (PFEM), first proposed in [12] and since then widely studied (see e.g. [8,9,54,13,11,53] and references therein), is one of the most adapted scheme to construct a mimetic finite-dimensional Dirac structure. Furthermore, it only relies on the well-proven and robust finite element method: it gives rise to sparse matrices, it is easy to implement, and one can take advantage of the numerous existing softwares.…”
Section: Structure-preserving Discretization: State Of the Artmentioning
confidence: 99%
“…Although PFEM was originally designed to mimic the Stokes-Dirac structure at the discrete level in [12] using vectorial calculus, it has also been rewritten in the formalism of exterior calculus in [13], which usually allows easier proofs of the aforementioned cohomology and topological decomposition preservations. It will be shown that together with the compatibility conditions between the spaces of approximations coming from cohomoly, PFEM leads to a very interesting result for the space discretization of pHs, given in Theorem 4.4.…”
Section: Structure-preserving Discretization: State Of the Artmentioning
confidence: 99%